Photodegradation process for the removal of acid orange 10 using titanium dioxide and bismuth vanadate from aqueous solution - B. Rahimi; A. Ebrahimi; N. Mansouri; N. Hosseini (Global Journal of Environmental Science and Management)
In this study, the photocatalytic degradation of azo-dye acid orange 10 was investigated using titanium dioxide catalyst suspension, irradiation with ultraviolet-C lamp and bismuth vanadate under visible light of light-emitting diode lamp. Response surface methodology was successfully employed to optimize the treatment of acid orange 10 dye and assess the interactive terms of four factors. The characteristics of catalysts were determined by field emission scanning electron microscopes, X-ray diffraction and Fourier transform infrared spectroscopy. The optimum values of initial dye concentration, initial pH, irradiation time and catalyst dose were found 11.889 mg/L, 4.592, 12.87 min, and 0.178 g/100 mL for ultraviolet/titanium dioxide process, respectively, and 10.919 mg/L, 3.231, 320.26 min and 0.239 g/100 mL for visible/bismuth vanadate process, respectively. The removal efficiencies obtained for acid orange 10 were 100% and 36.93% after selecting the optimized operational parameters achieved for titanium dioxide and bismuth vanadate, respectively. The highest efficiency was achieved by the use of ultraviolet/titanium dioxide system, while a low acid orange 10 removal efficiency was obtained for the synthesized bismuth vanadate using the co-precipitation method. Thus, it seems necessary to increase the photocatalytic activity of bismuth vanadate in combination with titanium dioxide to remove acid orange 10 dye in subsequent studies.